Low-dust high-strength gypsum-based putty and preparation method thereof

A low-dust, high-strength gypsum-based putty formulation addresses environmental and quality issues by using specific components and preparation methods, reducing dust and improving strength, thus enhancing construction site safety and quality.

CN119220122AActive Publication Date: 2024-12-31NIPPONPAINT SICHUAN CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310789803.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

Existing gypsum-based putty products generate high dust, crack easily, and have low strength, posing environmental and quality challenges in construction sites.

Method used

A low-dust, high-strength gypsum-based putty formulation comprising β-desulfurized gypsum powder, ordinary white sand, calcium powder, composite dust suppression components, rubber powder, and water retaining agent, optimized with specific ratios and preparation methods to reduce dust and enhance strength.

Benefits of technology

The formulation significantly reduces dust generation and improves construction site environmental safety while enhancing strength and construction quality, meeting regulatory standards for dust and strength requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004313276280000051
    Figure BDA0004313276280000051
Patent Text Reader

Abstract

The invention relates to low-dust high-strength gypsum-based putty and a preparation method thereof. The low-dust high-strength gypsum-based putty comprises the following components in parts by weight: beta-desulfurized gypsum powder, ordinary white sand, calcium powder, a composite dust suppression component, rubber powder, a water-retaining agent and an auxiliary agent, the composite dust suppression component comprises polyether, alkyl sulfate and alkaline inorganic matter; wherein the weight ratio of the polyether to the alkyl sulfate to the alkaline inorganic matter is (1-3): (2-5): (5-8); the polyether is polyoxyethylene; the alkyl sulfate is dodecyl sulfate; the alkaline inorganic matter is calcium hydroxide. According to the invention, the environmental influence of large dust raising of gypsum-based putty on a construction site is solved, and the engineering quality problems of cracking, low strength, powder falling and the like during construction are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gypsum-based mixed mortar, and in particular to a low-dust high-strength gypsum-based putty and a preparation method thereof. Background Art

[0002] The current market has increasingly stringent requirements for construction site environmental management and construction product quality management. Gypsum-based putty is a widely used leveling material for interior wall leveling, and its quality directly affects the construction site environment and construction quality. However, existing gypsum-based putty generally has problems such as easy dust generation during mixing, cracking after construction, low strength, and powder loss, which have a serious impact on the quality of the project. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a low-dust and high-strength gypsum-based putty and a preparation method thereof, so as to solve the environmental impact of high dust caused by the gypsum-based putty at the construction site, and solve the engineering quality problems such as cracking, low strength, and powdering during construction.

[0004] To solve the above problems, the present invention is implemented through the following technical solutions:

[0005] The first invention object of the present invention is:

[0006] Provided is a low-dust, high-strength gypsum-based putty comprising the following components in parts by weight:

[0007] β-desulfurized gypsum powder 280-600 parts, ordinary white sand 120-300 parts, calcium powder 100-400 parts,

[0008] 5-30 parts of composite dust suppression component, 5-30 parts of rubber powder, 1-4 parts of water retaining agent, 2-5 parts of auxiliary agent;

[0009] The composite dust suppression components include: polyether, alkyl sulfate, alkaline inorganic substances;

[0010] The weight ratio of the polyether, alkyl sulfate and alkaline inorganic substance is:

[0011] Polyether: alkyl sulfate: alkaline inorganic matter = 1-3: 2-5: 5-8;

[0012] The polyether is polyethylene oxide (PEO);

[0013] The alkyl sulfate is dodecyl sulfate;

[0014] The alkaline inorganic substance is calcium hydroxide (Ca(OH)2).

[0015] A preferred example of the low-dust high-strength gypsum-based putty of the present invention is:

[0016] The low-dust high-strength gypsum-based putty comprises the following components in parts by weight:

[0017] 400-500 parts of β-desulfurized gypsum powder, 180-240 parts of ordinary white sand, 200-400 parts of calcium powder, 10-20 parts of composite dust suppression components, 8-18 parts of rubber powder, 2-3 parts of water retaining agent, and 3-4 parts of additives;

[0018] The composite dust suppression components include: polyether, alkyl sulfate, alkaline inorganic substances;

[0019] The weight ratio of the polyether, alkyl sulfate and alkaline inorganic substance is:

[0020] Polyether: alkyl sulfate: alkaline inorganic matter = 1-3: 2-5: 5-8;

[0021] The polyether is polyethylene oxide (PEO);

[0022] The alkyl sulfate is dodecyl sulfate;

[0023] The alkaline inorganic substance is calcium hydroxide (Ca(OH)2).

[0024] The low-dust high-strength gypsum-based putty of the present invention is further optimized as follows:

[0025] The percentage of the composite dust suppression component in the total weight of the low-dust high-strength gypsum-based putty cannot exceed 3%.

[0026] The low-dust high-strength gypsum-based putty of the present invention is further optimized as follows:

[0027] The polyether is polyethylene oxide (PEO) with a relative molecular mass of 10 5 ~10 7 between; and / or

[0028] The alkyl sulfate is one or a combination of sodium dodecyl sulfate, potassium dodecyl sulfate, ammonium dodecyl sulfate; and / or

[0029] The β-desulfurized gypsum powder comprises the following components in weight percentage:

[0030] The content of soluble anhydrous gypsum AⅢ is less than 5%, the content of hemihydrate gypsum HH is higher than 85%, the residual dihydrate gypsum DH is less than 4%, the attached water should be less than 1%, and the rest is impurities;

[0031] The purity of β-desulfurized gypsum powder should be >90%; (Purity refers to the CaSO4 content in β-desulfurized gypsum powder)

[0032] The initial setting time should be between 4 and 30 minutes, and the final setting time should be between 5 and 30 minutes;

[0033] Flexural strength should be >3MPa, compressive strength should be >6MPa; and / or

[0034] The rubber powder is a redispersible latex powder based on vinyl acetate and ethylene copolymer; and / or

[0035] The viscosity of the water retaining agent should be between 60000 and 80000 mPa.s; and / or

[0036] The auxiliary agent includes a protein-based high-efficiency gypsum retarder; and / or

[0037] The stone powder content of the sieve residue of the ordinary white sand is strictly controlled to be less than 2% by mass percentage.

[0038] The second object of the present invention is:

[0039] Provided is a method for preparing the aforementioned low-dust, high-strength gypsum-based putty:

[0040] Put β-desulfurized gypsum powder, ordinary white sand, calcium powder, composite dust suppression component, rubber powder, water retaining agent and additives into a dry powder mixer in proportion, mix them evenly, and prepare a low-dust high-strength gypsum-based putty;

[0041] The composite dust suppression component comprises the following preparation steps:

[0042] S1. Put the alkaline inorganic substance into a dry powder mixing mixer at a temperature of 23±2°C and a relative humidity of 90%, and start the machine for pretreatment for 400 seconds to allow a certain amount of water to be adsorbed on its surface;

[0043] S2. The alkyl sulfate is added to a mixer and mixed for 400 seconds to allow the hydrophilic groups in the alkyl sulfate to adsorb on the attached water on the surface of the alkaline inorganic substance, and then the polyether is added and mixed for 400 seconds to allow the head groups of the alkyl sulfate to adsorb;

[0044] S3. Place the mixed components in a 60°C constant temperature drying oven and dry them until the moisture content by mass is ≤1% to obtain a composite dust suppression component.

[0045] The low-dust high-strength gypsum-based putty prepared by the present invention has less dust when mixed with water and excellent construction performance after mixing. At the same time, the present invention meets the harmful substance limit standards for putty in GB / T 28627-2012 base plastering gypsum type B and GB18582-2020 harmful substances in building wall coatings.

[0046] The present invention has significant significance for construction site environmental management and construction personnel protection, and solves the problems of cracking, low strength and the like that are easy to occur during construction. DETAILED DESCRIPTION

[0047] In order to make the application, technical scheme and advantages of the present invention clearer, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not limited to the present invention. All simple improvements to the preparation method of the present invention under the premise of the present invention are within the protection scope of the present invention.

[0048] Example 1

[0049] A method for preparing low-dust high-strength gypsum-based putty:

[0050] Put β-desulfurized gypsum powder, ordinary white sand, calcium powder, composite dust suppression component, rubber powder, water retaining agent and additives into a dry powder mixer in proportion, mix them evenly, and prepare a low-dust high-strength gypsum-based putty;

[0051] The composite dust suppression component comprises the following preparation steps:

[0052] S1. Put the alkaline inorganic substance into a dry powder mixing mixer at a temperature of 23±2°C and a relative humidity of 90%, and start the machine for pretreatment for 400 seconds to allow a certain amount of water to be adsorbed on its surface;

[0053] S2. Add alkyl sulfate into a mixer and mix for 400 seconds to allow the hydrophilic groups in the alkyl sulfate to adsorb on the attached water on the surface of the alkaline inorganic substance (Ca(OH)2), and then add polyether [polyethylene oxide (PEO)] and mix for 400 seconds to allow it to adsorb on the head group of the alkyl sulfate;

[0054] S3. Place the mixed components in a 60°C constant temperature drying oven and dry them until the moisture content by mass is ≤1% to obtain a composite dust suppression component.

[0055] Its specific composition is shown in the following table (parts by weight):

[0056]

[0057] Among the experimental groups 1# to 3#: the alkyl sulfate was sodium dodecyl sulfate;

[0058] Among the experimental groups 4# to 6#: the alkyl sulfate was potassium dodecyl sulfate;

[0059] Dust mass concentration test: Use Beidouxing portable dust concentration detector HBD5SPM4210-DS-A03 for testing

[0060] Standard tensile bond strength test: Test according to Type B in GB / T 28627-2012

[0061] Flexural / compressive strength test: Tested according to Type B in GB / T 28627-2012

[0062] The test results of the embodiment are shown in the following table:

[0063] Example <![CDATA[Dust mass concentration mg / m 3 > Standard tensile bond strength MPa Flexural strength MPa Compressive strength MPa 1# 2.85 0.85 2.82 5.91 2# 2.69 0.83 2.88 6.11 3# 2.42 0.87 2.96 5.98 4# 2.84 0.91 2.78 5.68 5# 2.79 0.88 2.71 5.82 6# 2.65 0.80 2.73 5.78

[0064] Comparative Examples 1 to 3 are provided below, and their preparation methods are the same as those of the examples, except that the composite dust suppression component in the examples is not used.

[0065] Its specific composition is shown in the following table (parts by weight):

[0066] composition Comparative Example 1 Comparative Example 2 Comparative Example 3 β-desulfurized gypsum powder 450 450 450 White sand 200 200 200 Calcium powder 323.5 323.5 323.5 Sodium Lauryl Sulfate 15 10 5 Polyethylene oxide / 5 5 <![CDATA[Ca(OH)2]]> / / 5 Rubber powder 6 6 6 Water Retention Agent 2.5 2.5 2.5 Additives 3 3 3

[0067] The test results of the comparative example are shown in the following table:

[0068] Comparative Example <![CDATA[Dust mass concentration mg / m 3 > Standard tensile bond strength MPa Flexural strength MPa Compressive strength MPa 1# 80.21 0.52 2.06 4.15 2# 78.95 0.47 2.15 4.21 3# 75.54 0.49 2.23 4.26

[0069] Through comparison, it is found that the dust mass concentration of the low-dust and high-strength gypsum-based putty provided by the present invention during stirring is much lower than that of conventional gypsum-based putty, which significantly improves the protection of construction workers and the construction site environment.

[0070] To sum up, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

[0071] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0072] The experimental methods without specific conditions in the present invention are usually carried out according to conventional conditions or conditions recommended by the manufacturer.

[0073] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.

[0074] Unless otherwise indicated, percentages and parts are by weight.

[0075] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.

[0076] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.

Claims

1. A low-dust, high-strength gypsum-based putty, characterized in that: It includes the following components by weight: 280-600 parts of β-desulfurized gypsum powder, 120-300 parts of ordinary white sand, 100-400 parts of calcium powder, 5-30 parts of composite dust suppression components, 5-30 parts of rubber powder, 1-4 parts of water retaining agent, and 2-5 parts of additives; The composite dust suppression components include: polyether, alkyl sulfate, alkaline inorganic substances; The weight ratio of the polyether, alkyl sulfate and alkaline inorganic substance is: Polyether: alkyl sulfate: alkaline inorganic matter = 1-3: 2-5: 5-8; The polyether is polyethylene oxide; The alkyl sulfate is dodecyl sulfate; The alkaline inorganic substance is calcium hydroxide.

2. The low-dust, high-strength gypsum-based putty according to claim 1, characterized in that: It includes the following components by weight: 400-500 parts of β-desulfurized gypsum powder, 180-240 parts of ordinary white sand, 200-400 parts of calcium powder, 10-20 parts of composite dust suppression components, 8-18 parts of rubber powder, 2-3 parts of water retaining agent, and 3-4 parts of additives; The composite dust suppression components include: polyether, alkyl sulfate, alkaline inorganic substances; The weight ratio of the polyether, alkyl sulfate and alkaline inorganic substance is: Polyether: alkyl sulfate: alkaline inorganic matter = 1-3: 2-5: 5-8; The polyether is polyethylene oxide; The alkyl sulfate is dodecyl sulfate; The alkaline inorganic substance is calcium hydroxide.

3. The low-dust, high-strength gypsum-based putty according to claim 1, characterized in that: The percentage of the composite dust suppression component in the total weight of the low-dust high-strength gypsum-based putty cannot exceed 3%.

4. The low-dust, high-strength gypsum-based putty according to claim 1, characterized in that: The polyether is polyethylene oxide, and the relative molecular mass is 10 5 ~10 7 between; and / or The alkyl sulfate is one or a combination of sodium dodecyl sulfate, potassium dodecyl sulfate, ammonium dodecyl sulfate; and / or The β-desulfurized gypsum powder comprises the following components in weight percentage: The content of soluble anhydrous gypsum AⅢ is less than 5%, the content of hemihydrate gypsum HH is higher than 85%, the residual dihydrate gypsum DH is less than 4%, the attached water should be less than 1%, and the rest is impurities; The purity of β-desulfurized gypsum powder should be > 90%; The initial setting time should be between 4 and 30 minutes, and the final setting time should be between 5 and 30 minutes; Flexural strength should be >3MPa, compressive strength should be >6MPa; and / or The rubber powder is a redispersible latex powder based on vinyl acetate and ethylene copolymer; and / or The viscosity of the water retaining agent should be between 60000 and 80000 mPa.s; and / or The auxiliary agent is a protein-based high-efficiency gypsum retarder; and / or The stone powder content of the sieve residue of the ordinary white sand is strictly controlled to be less than 2% by weight.

5. A method for preparing the low-dust, high-strength gypsum-based putty according to claim 1, characterized in that: Put β-desulfurized gypsum powder, ordinary white sand, calcium powder, composite dust suppression component, rubber powder, water retaining agent and additives into a dry powder mixer in proportion, mix them evenly, and prepare a low-dust high-strength gypsum-based putty; The composite dust suppression component comprises the following preparation steps: S1. Put the alkaline inorganic substance into a dry powder mixing mixer at a temperature of 23±2°C and a relative humidity of 90%, and start the machine for pretreatment for 400 seconds to allow a certain amount of water to be adsorbed on its surface; S2. The alkyl sulfate is added to a mixer and mixed for 400 seconds to allow the hydrophilic groups of the alkyl sulfate to adsorb on the attached water on the surface of the alkaline inorganic substance, and then the polyether is added and mixed for 400 seconds to allow the head groups of the alkyl sulfate to adsorb; S3. Place the mixed components in a 60°C constant temperature drying oven and dry them until the moisture content by mass is ≤1% to obtain a composite dust suppression component.

Citation Information

Patent Citations

  • Desulfurized gypsum-based light-weight, high-strength and sound-absorbing plastering material and preparation method thereof

    CN105503109A

  • Preparation method of water absorption and wetting type environment-friendly dust suppressant

    CN108441173A

  • Light underlying plastering gypsum mortar and preparation method thereof

    CN109809785A

  • Low-cost gypsum-based self-leveling material

    CN113603442A

  • Wet polishing and light receiving gypsum-based putty as well as preparation and use methods thereof

    CN114591057A